A THz Metamaterial Absorber with Multiple Polarization - Insensitive, Sensitive, and Tunable - Ayesha Mohanty; Om Prakash Acharya; Bhargav Appasani; Kriangkrai Sooksood; Sushanta Kumar Mohapatra (My University, 2021)
Terahertz (THz) absorbers are gaining interest in many applications. In this paper, we present the design and simulation of a multiband metamaterial absorber (MMA) with combined polarization properties and prominent absorption at 2.2 THz and 3.9 THz. The MMA comprises two square split-ring resonators and one square ring resonator placed on top of a polyimide dielectric spacer, offering multiband absorption characteristics with maximum absorptivity of 93.18% and 96.09%, respectively. The most protruding feature of this design is that it displays multiple polarization characteristics, including insensitivity, sensitivity, and tunability, even though the structure is similar to those of conventional absorbers. Firstly, the distinctly visible absorption spectra at 1.8 THz, gradually diminishes with an increase in polarization angle and then completely vanishes for TM polarization. Secondly, the prominent band at 2.2 THz is insensitive to changes in polarization of the incident wave, whereas, at 3.9 THz, the absorption band displays polarization tunability characteristics. Due to the multiple characteristics displayed by the structure, this MMA can be simultaneously used for several applications in the terahertz frequency regime such as imaging, terahertz spectroscopy, sensing, and stealth technology.
Keywords: Molar absorptivity; Split-ring resonator; Brewster's angle; Absorption band; Metamaterials and Metasurfaces Applications